POLA KOMUNIKASI KOMUNITAS PELESTARI REOG PONOROGO DALAM MEMPERTAHANKAN SOLIDARITAS ANGGOTANYA - Indriyanti, Laras; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium; Vol 4 No 1 (2023): Jurnal Ilmu Komunikasi Vol 4 No 1 Tahun 2023, 2023)
ABSTRACT This study aims to explain and find out the communication patterns carried out by the Reog Sardulo Mbalelo Bali community in increasing the solidarity of its members. This study uses a qualitative descriptive approach with purposive sampling informant determination technique. Data obtained from interviews, observations, documentation and literature study. The analytical technique used in this research is qualitative data analysis. The results showed that the Reog Sardulo Mbalelo Bali community used three communication patterns, namely the wheel communication pattern and the Y pattern in formal activities and the star communication pattern in informal activities. The star's communication pattern further strengthens their solidarity. Keywords: Communication Pattern, Reog Sardulo Mbalelo Bali Community, Member Solidarity